2-Benzhydryl-6-tert-butyl-4-methylphenol - Yoon, Sungwoo (International Union of Crystallography, 2013)
The title compound, C(24)H(26)O, was prepared by the reaction between 2-tert-butyl-4-methylphenol and diphenylmethanol in the presence of sulfuric acid. Three benzene rings are attached directly to the central C—H group in a twisted propeller conformation with the local pseudo-C (3) rotational axis coinciding with the C—H bond. There are three short C—H⋯O contacts in the molecule.